2021
DOI: 10.3390/ijerph182111370
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sleep Quality on Pain in Chilean Individuals with Musculoskeletal Disorders

Abstract: Poor sleep quality (SQ) negatively affects pain associated with musculoskeletal disorders (MSD). As the level of economic development of a country determines its sanitary conditions, these can influence the sleep–pain relationship; therefore, it is relevant to generate evidence in the population with MSD in developing countries. This cross-sectional study sought to determine the effect of poor SQ on pain in Chilean individuals with MSD, controlling for sex and duration of pain (in months). Method: A total of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The literature review revealed that chronic shoulder pain was linked sleep disorders in 5 of the selected studies ( Cho et al, 2013 ; Mulligan et al, 2015 ; Khazzam et al, 2018 ; Toprak and Erden, 2019 ; Hwang and Oh, 2022 ); however, no treatment strategies were proposed to alleviate pain and improve sleep these patients. These findings are consistent with the studies by Schuh-Hofer et al (2013) and Bascour-Sandoval et al (2021) where the authors noted the high prevalence of sleep disorders in people with chronic pain. The quality and quantity of sleep are important biological resources for regulating pain homeostasis processes ( Haack et al, 2007a ).…”
Section: Discussionsupporting
confidence: 93%
“…The literature review revealed that chronic shoulder pain was linked sleep disorders in 5 of the selected studies ( Cho et al, 2013 ; Mulligan et al, 2015 ; Khazzam et al, 2018 ; Toprak and Erden, 2019 ; Hwang and Oh, 2022 ); however, no treatment strategies were proposed to alleviate pain and improve sleep these patients. These findings are consistent with the studies by Schuh-Hofer et al (2013) and Bascour-Sandoval et al (2021) where the authors noted the high prevalence of sleep disorders in people with chronic pain. The quality and quantity of sleep are important biological resources for regulating pain homeostasis processes ( Haack et al, 2007a ).…”
Section: Discussionsupporting
confidence: 93%
“…Bodily pain and general health (i.e., physical health components) were associated with sleep quality, but not bodily function and physical role. Poor sleep quality has been linked to a greater perception of pain, both in athletes (Bascour-Sandoval, Norambuena-Noches, et al, 2021) and individuals with musculoskeletal disorders (Alsaadi et al, 2014;Bascour-Sandoval, Belmar-Arriagada, et al, 2021), which, added to the decrease in mental health, would explain the reduced perception of overall health within the physical components. Potter et al (2020) found that poor sleep quality was associated with higher levels of interference with pain and pain intensity, but not in the domain of physical function/mobility, on the quality of life questionnaire, "Patient-Reported Outcome Measurement Information System" (PROMIS).…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with neuropathic pain, those with poor sleep quality experience more pain, more severe depressive states, and worse quality of life than patients with good sleep quality, with a positive correlation between sleep quality and emotional state ( 43 ). In patients with musculoskeletal disorders, poorer sleep quality is associated with higher pain levels, and a high frequency of poor sleep quality is more prevalent in females ( 44 ). Another study has also found that sleep deficiency, particularly insomnia and poor sleep quality, might modify the effectiveness of psychological treatments for CP ( 45 ).…”
Section: Clinical Research On the Relationship Between Chronic Pain A...mentioning
confidence: 99%
“…The coexistence of insomnia and chronic musculoskeletal pain results in greater pain intensity and alterations in sleep homeostasis (42). Among patients with neuropathic pain, those with poor sleep quality experience more pain, more severe depressive states, and worse quality of life than patients with good sleep quality, with a positive correlation between sleep quality and emotional state (43). In patients with musculoskeletal disorders, poorer sleep quality is associated with higher pain levels, and a high frequency of poor sleep quality is more prevalent in females (44).…”
Section: Consequences Of Chronic Pain Combined With Sleep Disordersmentioning
confidence: 99%